2018
DOI: 10.1088/1674-1056/27/8/080502
|View full text |Cite
|
Sign up to set email alerts
|

Double compound combination synchronization among eight n-dimensional chaotic systems

Abstract: Depending on double compound synchronization and compound combination synchronization, a new kind of synchronization is introduced which is the double compound combination synchronization (DCCS) of eight n-dimensional chaotic systems. This kind may be considered as a generalization of many types of synchronization. In the communication, based on many of drive and response systems, the transmitted and received signals will be more secure. Using the Lyapunov stability theory and nonlinear feedback control, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…e paper then proceeds with data analysis and findings. e final three parts describe significant results, limits, theory, and practice reflection and pave the path for future study [24][25][26].…”
Section: Objectivesmentioning
confidence: 99%
“…e paper then proceeds with data analysis and findings. e final three parts describe significant results, limits, theory, and practice reflection and pave the path for future study [24][25][26].…”
Section: Objectivesmentioning
confidence: 99%
“…In 2018, Mahmoud et al [77] introduced double compound combination synchronization of eight chaotic systems according to double compound synchronization and compound combination synchronization as follows,…”
Section: H Combination Synchronization and Its Extensionsmentioning
confidence: 99%
“…Since Runzi et al [28] revealed the combination synchronization scheme, the synchronization of multi-drive and multi-response systems, multi-drive and single-response systems, single-drive and multi-response systems are suggested. Later, some new synchronization schemes appeared and have been developed by leaps and bounds, such as the combination-combination [29][30][31][32], compound synchronization [33][34][35] and double compound synchronization [36,37], etc. It can be said to be a major breakthrough in the field of chaos synchronization.…”
Section: Introductionmentioning
confidence: 99%